Effect of Blood Cadmium Level on Mortality in Patients Undergoing Maintenance Hemodialysis. Issue 42 (October 2015) - Hsu, Ching-Wei; Yen, Tzung-Hai; Chen, Kuan-Hsing; Lin-Tan, Dan-Tzu; Lin, Ja-Liang; Weng, Cheng-Hao; Huang, Wen-Hung
Abstract : Abstract: Previous studies of general populations indicated environmental exposure to low-level cadmium increases mortality. However, the effect of cadmium exposure on maintenance hemodialysis (MHD) patients is unclear. A total of 937 MHD patients from 3 centers in Taiwan were enrolled in this 36-month observational study. Patients were stratified by baseline blood cadmium level (BCL) into 3 groups: high BCL (>0.521 μg/L; n = 312), intermediate BCL (0.286−0.521 μg/L; n = 313), and low BCL (<0.286 μg/L; n = 312). The mortality rates and causes of death were analyzed. The analytic results demonstrated patients in the high BCL group had a significantly higher prevalence of malnutrition and inflammation than patients in the low and intermediate BCL groups. After 3 years of follow-up, 164 (17.5%) patients died and the major cause of death was cardiovascular disease. A Cox multivariate analysis indicated the high BCL group had increased hazard ratios (HRs) for all-cause mortality (HR = 1.72; 95% confidence interval [CI]: 1.14–2.63; P  = 0.018), cardiovascular-related mortality (HR = 1.85; 95% CI: 1.09–3.23; P  = 0.032), and infection-related mortality (HR = 2.27; 95% CI: 1.12–4.55; P  = 0.035). A Cox multivariate analysis of MHD patients who never smoked (n = 767) indicated the high BCL group had increased HRs for all-cause mortality (HR = 1.67; 95% CI: 1.04–2.63; P  = 0.048) and cardiovascular-related mortality (HR = 2.08; 95% CI: 1.08–4.00; P  = 0.044). In conclusion, BCL is an important determinant of mortality in MHD patients. Therefore, MHD patients should avoid cadmium exposure as much as possible, such as tobacco smoking and eating cadmium-containing foods.